Defects in affordable housing projects in Klang Valley, Malaysia - Abdul-Rahman, H; Wang, C; Wood, LC; Khoo, YM (American Society of Civil Engineers (ASCE), 2012)
Several affordable housing programs have been introduced by the government to achieve the objectives of several Malaysia Plans; however, the success of the housing programs has been reduced due to readily reported quality problems and defects. This research aims to identify the types of defects in affordable housing and determine what is causing the defects, so that solutions may be devised to raise the quality of housing stock in Malaysia. A questionnaire survey was distributed to 310 residents of affordable housing, located in four different regions in Klang Valley, Malaysia. The most commonly occurring defects in affordable housing are leaking pipes, total failure of water supply systems, cracking in concrete walls, faulty door knobs, and dampness to concrete walls. This suggests that improvements in workmanship, the use of superior materials, and changes to more customer-oriented supervision and monitoring may reduce the incidence of defects. Local conditions, such as heavy rainfall, may influence dampness, and may reduce the generalizability of findings to other areas with different weather patterns. The findings have been reported to the Construction Industry Development Board of Malaysia to improve the quality of affordable housing.
Keywords: Defects dissection; Low cost housing; Affordable housing; Building defects; Building quality